The impact of ICT capital and use on economic growth - Wesam M. Sedika; Waleed Emamb (International Telecommunications Society (ITS), 2019)
This paper investigates how ICT capital and usage affects economic growth which is currently received considerable attention in the information society and its potential impacts on the economic growth. A sample of MENA and OECD countries including developing, emerging, and developed countries is used in this study to determine the impact of ICT on economic growth during the last 15 years using panel data analysis. This research provides statistical evidence for the impact of labor and capital on economic growth as reported in several previous studies. However, this impact differ between regions and level of development. It is observed that the impact of ICT on economic growth for OECD, emerging and advanced economies is higher than its impact in MENA and developing countries. This is contradicting to the impact of non-ICT capital where the impact of non-ICT capital on economic growth for OECD and advanced economies is much smaller than its value for MENA and developing countries. In addition, both mobile service and fixed broadband service as a measures for ICT usage show positive and significant impact on economic growth. This impact appears in OECD countries and advanced economies only but not appears in MENA countries and developing economies.
Keywords: 330; ICT; economic growth; panel data analysis